Academic performance in adolescents aged 15–16 years born after frozen embryo transfer compared with fresh embryo transfer: a nationwide registry‐based cohort study. (24th October 2018) - Spangmose, AL; Malchau, SS; Henningsen, AA; Forman, JL; Rasmussen, S; Loft, A; Schmidt, L; Pinborg, A
Abstract : Objective: To assess academic performance in singletons aged 15–16 years conceived after frozen embryo transfer (FET) compared with singletons born after fresh embryo transfer (ET) in Danish cohorts born from 1995 to 2001. Design: Danish national registry‐based cohort study. Setting: Danish national registries. Population: All 6495 singletons conceived after assisted reproductive technology (ART) treatment in Denmark from 1995 to 2001 [FET ( n ) = 423; fresh ET ( n ) = 6072]. Methods: Mean test scores on a national standardised and international comparable grading‐scale. Comparisons of test score were first made in univariate analysis (Model 1) and secondly in a multivariate linear model (Model 2) adjusting for relevant reproductive and socio‐demographic covariates such as the occupational and educational level of the parents. Sensitivity analyses on FET‐IVF (in vitro fertilisation) versus fresh ET‐IVF and FET‐ICSI (intracytoplasmic sperm injection) versus fresh ET‐ICSI were made. Linear mixed models were used to account for the correlation in test scores of siblings for continuous outcome. Main outcome measures: Mean overall test score and test score in Danish, mathematics, English, and physics/chemistry. Results: Crude and adjusted mean test scores were similar for adolescents conceived after FET compared with fresh ET. The crude mean difference was +0.11 (95% CI −0.11; 0.34), and the adjusted mean difference was +0.12 (95% CI −0.09; 0.34). Conclusions: Adolescents conceived after FET had similar academic performance at 15–16 of years of age compared with children conceived after fresh ET. Tweetable abstract: Using frozen embryos in fertility treatment does not affect school performance in Danish adolescents aged 15–16 years. Tweetable abstract: Using frozen embryos in ART treatment does not affect school performance in Danish adolescents aged 15–16 years.